Efecto de la temperatura en el daño geomecánico (2017)
It is well known that changes in the pore pressure associated with hydrocarbon exploitation can cause reversible or irreversible modification of the stress-dependent permeability in the reservoir, which is known as geomechanical damage. This investigation evaluates the scenario where besides the pore pressure variation, the reservoir also experiences thermal alteration. This scenario is commonly meet during thermal recovery projects performed in different heavy oil reservoirs in Colombia; since most of the oil production in Colombia comes from heavy oil reservoirs, the topic addressed in this investigation is of grater importance for the oil industry in the country. This master’s thesis has the main objective to develop a computational model in order to evaluate the effect of temperature on the geomechanical damage. To achieve this objective, a single-well simulator that integrates the fields of pressure, temperature, and stress was developed. Furthermore, the simulator also considers the elastoplastic behavior of the rock. The approach for integrating the three aforementioned fields involved an implicit fully coupling between stress and pressure, while the temperature remained as a known input variable which was included in the system of equation explicitly. Since the investigation is focused in the geomechanical damage and not in the proper modeling of temperature propagation, the above approach is considered appropriated to tackle the objective of this master’s thesis. The developed simulator was preliminary validated with analytical solutions obtaining good results. Finally, a series of study cases were presented in the results section in order to prove the capabilities of the simulator to study the effect of temperature on the geomechanical damage in a poorly consolidated sand heavy oil reservoir. The results showed that, additional to the geomechanical damage induced by pore pressure alteration, the temperature changes can also cause geomechanical damage in the reservoir. This thermally induced geomechanical damage can be reversible due to thermal expansion of the rock or irreversible due to shear dilation of the rock. However, the chosen parameters and boundary conditions for the study cases lead to small changes in productivity in spite of the observed geomechanical damage; which evidenced the need for identifying in further investigations the scenarios where the geomechanical damage play a more dramatic role in the productivity of the reservoir.